Singing in my soul : black gospel music in a secular age - Jackson, Jerma A. (African American music reference., 2004)
Black gospel music grew from obscure nineteenth-century beginnings to become the leading style of sacred music in black American communities after World War II. Jerma A. Jackson traces the music's unique history, profiling the careers of several singers and demonstrating the important role women played in popularizing gospel.